LANGUAGE AND MEMORY IN PSYCHOLINGUISTICS - S. Nurmanova (American Journals, 2024)
The article explores language and memory psycholinguistically. The strengths or weaknesses of memory in humans have been studied as 4 types.
Keywords: Experiment, psychological experiment, perception, psyche, memory, language, verbal memory, schematization.